Estimated daily intake and safety of FD&C food-colour additives in the US population. Issue 6 (3rd June 2017) - Bastaki, Maria; Farrell, Thomas; Bhusari, Sachin; Bi, Xiaoyu; Scrafford, Carolyn
ABSTRACT: A refined exposure assessment was undertaken to calculate the estimated daily intake (EDI) of the seven FD&C straight-colour additives and five FD&C colour lakes ('synthetic' food colours) approved in the United States. The EDIs were calculated for the US population as a whole and specific age groups, including children aged 2–5 and 6–12 years, adolescents aged 13–18 years, and adults aged 19 or more y. Actual use data were collected from an industry survey of companies that are users of these colour additives in a variety of products, with additional input from food colour manufacturers. Food-consumption data were obtained from the National Health and Nutrition Examination Survey (NHANES). The assessment was further refined by adjusting the intake to more realistic scenarios based on the fraction of products containing colour within specific food categories using data provided by the Mintel International Group Ltd. The results of the analysis indicate that (1) the use levels reported by the industry are consistent with the concentrations measured analytically by the US Food and Drug Administration; and (2) exposure to food-colour additives in the United States by average and high-intake consumers is well below the acceptable daily intake (ADI) of each colour additive as published by the Joint WHO/FAO Committee on Food Additives (JECFA) and allows wide margins of safety. It is concluded that food colour use as currently practised in the United States is safe and does not result in excessive exposure to the population, even at conservative ranges of food consumption and levels of use.